Computational Fluid Dynamic (CFD) Analysis On Window Area Variation And Cooler Placement On Thermal Comfort In Stainless Steel Railway Carriages - Jayanto, Denni Bagus; Saleh, Arif Rahman; Dewi, Rany Pupita (Politeknik Negeri Lhokseumawe, 2024)
Thermal comfort is one of the most important factors in carrying out activities, especially during train travel. Therefore, PT Kereta Api Indonesia is trying to improve service standards by providing air conditioning on all trains, both executive and economy class. Several factors influence thermal comfort, such as temperature, air velocity, clothing insulation, radiation temperature, metabolism, and air humidity. This study aims to determine the distribution of temperature, air velocity, and airflow in stainless steel railroad cars, both actual and its variations. Computational Fluid Dynamic (CFD) simulation is used in this research. In the CFD simulation, several carriage design variations were applied, namely the actual design and three other designs that changed the location of the cooler and the window area like a commercial airplane. This study showed that KA 3 has a better temperature distribution with an average temperature of 24.71oC, and the airflow flows evenly throughout the carriage with an average speed of 0.50 m/s. According to SNI 03-6572-2001, KA 3 has met the comfort criteria.